PEMIKIRAN ESSENSIALISME DALAM PENDIDIKAN ISLAM - Khoiriyah, Istianatul; Bagas Mukti Nasrowi; Muhammad Hufron (STAI Pelabuhan Ratu, 2025)
The value crisis in contemporary education has become a crucial issue characterized by the weakening of moral orientation, the erosion of teacher authority, and the dominance of flexible approaches that ignore the basic principles of education. Departing from this phenomenon, this research aims to examine the thought of essentialism in Islamic education as a conceptual alternative that emphasizes traditional values, discipline, and a clear curriculum structure. This research uses a qualitative method with a library research approach, which is conducted through an in-depth review of relevant primary and secondary literature. The results show that essentialism in Islamic education emphasizes three main findings: the importance of education grounded in traditional and permanent values; the central role of the teacher as a moral and scientific authority; and curriculum and learning methods that focus on mastering core material and forming discipline. The study concludes that essentialism can provide a more stable, structured and valuable direction for education in the face of the challenges of modernity. Therefore, it is suggested that this essentialist approach be considered in the formulation of Islamic education policy and further developed through empirical research in the realm of practice. Keywords: Essentialism; philosophy; Islamic education